Hysteresis in economic relationships: An overview - Wolfgang Franz (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
This paper provides an overview of the hysteresis phenomenon in economics. After a brief formal statement the origins of this principle are outlined. Hysteresis in economic relationships is then discussed with special reference to industrial economics in an international setting and to labour economics. The paper concludes with an overview of papers to be published in a forthcoming special issue of the journal "Empirical Economics" (1990), for which this survey has been written as an introductory chapter.
Keywords: 330